(untitled) (Journal of human and social sciences, 2025)
A patent is one of the essential components of intellectual property. The inventor presents a novel idea to society, representing one of the most significant products of human intellect. Patents play a critical role in promoting creativity and innovation for economic development, particularly in the field of modern technology. A patent is the optimal legal tool to confer legal protection on an invention, granting the inventor the right to exploit it and enter into related transactions and contracts. However, the holder of a patent may face infringement of their rights by third parties or may become involved in disputes arising from the execution of contracts related to the patent, such as licensing, leasing, selling, or using it as a capital share in a company. Given the complex nature of patent disputes, including the rapid technological advancements and the confidentiality of information, litigation may not always be the most suitable mechanism for resolving such disputes. Traditional court proceedings are often slow, procedurally complex, public, and costly. In contrast, arbitration may offer a more appropriate forum for resolving these disputes due to its speed, confidentiality, specialization, and the international character that often defines such cases. However, during the arbitration of such contracts, the issue of the invalidity of the patent may be raised, and the arbitrator may be asked to rule on the nullity of the patent. Opinions differ on this matter: • Some argue that the authority to determine the validity of a patent lies exclusively with the administrative body that issued it. • Others believe it falls within the jurisdiction of the administrative judiciary. • A third view supports the arbitrator’s authority to decide on the validity or invalidity of a patent. Each opinion is supported by its own arguments and legal reasoning. To reach a convincing and reasoned conclusion, it is necessary to examine the concepts of arbitration and patents, the legal nature of patents, and whether they establish a new right for the inventor or merely recognize a pre-existing one. Furthermore, it must be determined whether a patent constitutes an administrative decision issued by the competent authority or a contract between the inventor and the state. This paper aims to explore these issues in depth to determine the scope of the arbitrator’s jurisdiction in patent disputes and propose what the author considers to be the most appropriate approach, while also urging the Libyan legislator to adopt it. This is particularly important given the ambiguity and lack of clarity in the current Libyan legal framework, as reflected in Article 31, paragraph (c) of Libyan Patent Law No. 8 of 1959. That provision addresses the expiration and nullity of patents, stating that a patent becomes void upon the issuance of a final and binding judgment, without specifying the nature of such judgment—whether judicial, arbitral, or both.